Bio-based epoxy resin wear-resistant anticorrosive coating composition as well as preparation method and application thereof
By using bio-based cashewol to prepare epoxy resin and adding modified SiO2 and SiC nanowhiskers, the problems of poor wear resistance and humidity sensitivity of the epoxy resin coating in high wear environments are solved, and the coating is significantly improved Wear resistance and corrosion resistance, suitable for centrifugal slurry pumps.
Patent Information
- Application Number
- CN202411246852.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
AI Technical Summary
Existing epoxy resin coatings are poorly abrasion resistant in high wear environments, are sensitive to humidity and may fail at extreme temperatures, and some chemicals will degrade, making it difficult to meet the wear resistance and corrosion protection needs of centrifugal slurry pumps .
Epoxy resin is prepared by using bio-based cashewol as raw material and reacted with formic acid, and enhanced by modifying SiO2 and SiC nanowhiskers to improve the wear resistance and corrosion resistance of the coating, combined with curing agent, defoaming agent and leveling agent Dispersed processing.
It significantly improves the wear resistance and corrosion resistance of the coating and reduces environmental pollution. It is suitable for centrifugal slurry pumps. The coating film shows good adhesion and impact resistance under high wear and extreme conditions.
Smart Images

Figure CN119144207A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a bio-based epoxy resin wear-resistant and anti-corrosion coating, and belongs to the field of organic coatings and composite materials. Background Art
[0002] A centrifugal slurry pump is a pump used to transport liquid containing solid particles (i.e. slurry). It uses centrifugal force to accelerate the slurry from the pump inlet through the impeller, push the liquid along the pump casing, and discharge it through the outlet. This pump is commonly used in industries such as mining, metallurgy, and chemicals, and the liquids it handles are usually dense and contain abrasives. The problems of wear resistance and corrosion resistance of centrifugal slurry pumps mainly occur in material selection and design. Since the pump handles slurries containing abrasives, wear-resistant materials are critical; and corrosion resistance requires the selection of suitable alloys or coatings to deal with chemical corrosion.
[0003] In the wear-resistant and anti-corrosion design of centrifugal slurry pumps, high-chromium cast iron alloys, tungsten alloys, nickel-chromium alloys and tungsten carbide alloys are commonly used. In terms of coatings, carbide coatings, ceramic coatings, polyurethane coatings and epoxy resin coatings are mainly used. Compared with other coatings, epoxy resin coatings have good corrosion resistance and are suitable for acidic or alkaline media environments. Although epoxy resin coatings have good corrosion resistance, they also have some disadvantages: they have poor wear resistance and are easily damaged in high-wear environments; they are sensitive to humidity and need to ensure a dry environment during construction; they may lose performance at extreme temperatures (high or low temperatures); and certain chemicals may cause them to degrade or fail. In order to improve the wear resistance and corrosion resistance of epoxy resin coatings, Zhang Ruizhu et al. prepared TiO2 / GF / EP composite materials by adding modified nano-TiO2 and glass flakes (GF) to the epoxy resin (EP) matrix. The microhardness of the composite coating with 4% nano-TiO2 and 30% GF was increased by 46.8% compared with pure EP, and the friction coefficient and mass loss after wear were reduced by 46.1% and 52.0% respectively compared with pure EP (Research on the wear resistance of epoxy resin synergistically enhanced by nano-titanium dioxide / glass flakes (Zhang Ruizhu, et al. Research on the wear resistance of epoxy resin synergistically enhanced by nano-titanium dioxide / glass flakes, Electroplating and Finishing, 2024, 43:84). How to further improve the wear resistance and corrosion resistance of the coating has become a hot topic in current research. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a bio-based epoxy resin wear-resistant and anti-corrosion coating and its use, so as to solve the above-mentioned problems existing in the prior art.
[0005] The present invention is achieved through the following technical solutions:
[0006] A bio-based epoxy resin wear-resistant and anti-corrosion coating composition comprises the following components in parts by weight:
[0007]
[0008] As a preferred embodiment, the preparation method of the epoxy resin is:
[0009] Mix cardanol and formic acid, stir at room temperature overnight, add hydrogen peroxide, and react to obtain a crude product;
[0010] The crude product was extracted with ethyl acetate, neutralized with saturated sodium bicarbonate solution, and the organic phase was collected;
[0011] The organic phase was dried over anhydrous sodium carbonate and concentrated under reduced pressure to obtain an epoxy resin.
[0012] As a preferred embodiment, the mass concentration of the hydrogen peroxide is 35%; the mass ratio of the cardanol to formic acid is (3-10): (1-3).
[0013] As a preferred embodiment, the preparation method of the modified SiO2 is:
[0014] After ammonia water, ethanol, deionized water and hexadecyltrimethylammonium bromide are mixed, tetraethyl orthosilicate and γ-glycidyloxypropyltrimethoxysilane are added, and the mixture is reacted at 50-60°C to obtain epoxidized SiO2;
[0015] Dispersing the epoxidized SiO2 in deionized water to obtain a SiO2 dispersion;
[0016] Dissolve octadecylamine in anhydrous ethanol, mix well, and add into the SiO2 dispersion. After reaction, modified SiO2 is obtained.
[0017] As a preferred embodiment, the mass ratio of the epoxidized SiO2 to octadecylamine is (2-4):(6-10).
[0018] As a preferred embodiment, the preparation method of the SiC nano whisker is:
[0019] Adding polyacrylonitrile and nano-SiO2 powder into N,N-dimethylacetamide solvent and dispersing them evenly, a precursor dispersion is obtained;
[0020] The precursor dispersion is subjected to low temperature quenching, and then transferred into ice water for extraction to remove the N,N-dimethylacetamide solvent, and then washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers;
[0021] The polyacrylonitrile / SiO2 composite nanofibers are heated to 250-350°C at a rate of 2-8°C / min in air, kept warm for 2 hours, then transferred to an argon atmosphere, heated to 650-750°C at a rate of 2-8°C / min, kept warm for 1 hour, and finally heated to 1200-1600°C at a rate of 8-12°C / min, kept warm for 1 hour to obtain SiC nanowhiskers.
[0022] As a preferred solution, the mass ratio of polyacrylonitrile to nano-SiO2 powder is (2-5):(1-2); the temperature of low-temperature quenching is -30--10°C, and the quenching time is 3-5h.
[0023] As a preferred solution, the curing agent is selected from fatty amine curing agents; the defoaming agent is selected from polysiloxane defoaming agents; and the leveling agent is selected from polyvinyl alcohol leveling agents.
[0024] A method for preparing the aforementioned bio-based epoxy resin wear-resistant and anti-corrosion coating composition comprises the following steps:
[0025] The modified SiO2, SiC nano whiskers and epoxy resin are added into distilled water, stirred and dispersed evenly at a speed of 500 rpm, and then a curing agent, a defoaming agent and a leveling agent are added and dispersed at a speed of 1000 rpm to obtain the bio-based epoxy resin wear-resistant and anti-corrosion coating.
[0026] A use of the aforementioned bio-based epoxy resin wear-resistant and anti-corrosion coating in a centrifugal wear-resistant slurry pump.
[0027] The basic implementation principle of the present invention is:
[0028] 1. Biodegradable cardanol is used as a raw material, reacted with formic acid and hydrogen peroxide, and epoxy groups are introduced into its side chains. Finally, under the condition of a curing agent, it is cured to obtain a bio-based epoxy resin.
[0029] 2. Using tetraethyl orthosilicate as a precursor, hexadecyltrimethylammonium bromide as a surfactant, and a silane coupling agent as an epoxidation group, hydrolyze under alkaline conditions to obtain epoxidized SiO2. The epoxidized SiO2 is reacted with octadecylamine to introduce amino groups on the surface of SiO2.
[0030] 3. Using polyacrylic acid and nano-SiO2 powder as precursors, polyacrylonitrile / SiO2 composite nanofibers were prepared by thermally induced phase separation. The fibers were then pre-oxidized, carbonized at low temperature, carbonized at high temperature and carbon thermally reduced to obtain silicon carbide nanowhiskers.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. Compared with ordinary epoxy resin, the system with cashew-based epoxy resin as the matrix is biodegradable, which greatly reduces the pollution to the environment.
[0033] 2. Introducing amino groups into the surface of SiO2 greatly improves the compatibility between inorganic powder SiO2 and matrix epoxy resin, and improves the physical and mechanical properties of the material.
[0034] 3. The addition of modified nano-SiO2 and SiC nano-whiskers greatly improves the wear resistance and corrosion resistance of epoxy resin, making the prepared coating applicable to centrifugal slurry pumps. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0036] Figure 1 This is the SEM photograph of the SiC nanowhiskers prepared in Example 1. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0038] Example 1
[0039] (1) Preparation of epoxy resin
[0040] 12g of cardanol was mixed with 4g of formic acid, stirred at room temperature overnight, and then 30mL of 35% hydrogen peroxide was added to the above solution. After the addition was completed, the reaction was stirred magnetically at 65°C for 1h, and the crude product was extracted with 100mL of ethyl acetate, and the product was neutralized with saturated sodium bicarbonate solution. The organic phase was collected, the product was dried with anhydrous sodium sulfate, and concentrated under reduced pressure to obtain a reddish brown viscous liquid epoxy resin.
[0041] (2) Preparation of modified SiO2
[0042] Add 3g ammonia water, 50g ethanol, 120g deionized water and 0.40g hexadecyltrimethylammonium bromide into a three-necked flask, add 2.0g tetraethyl orthosilicate and 0.7g Γ-glycidyloxypropyltrimethoxysilane under stirring, heat to 55℃, and react with magnetic stirring for 24h. The product is centrifuged, washed and dried to obtain epoxidized SiO2 white powder. Dissolve 0.30g epoxidized SiO2 in 120mL deionized water and disperse ultrasonically to obtain SiO2 dispersion; dissolve 0.60g octadecylamine in 100mL anhydrous ethanol. Add the octadecylamine solution to the SiO2 dispersion, react with magnetic stirring at 25℃ for 24h, wash and dry the product to obtain modified SiO2 white powder.
[0043] (3) Preparation of SiC nanowhiskers
[0044] Add 1g polyacrylonitrile and 0.2g nano-SiO2 powder to 20g N,N-dimethylacetamide solvent, and stir the solution magnetically at room temperature to obtain a precursor dispersion. Quench the dispersion in a -20℃ low-temperature refrigerator for 3h, then extract it in ice water, remove the solvent, soak it in distilled water for 24h, wash and dry it to obtain polyacrylonitrile / SiO2 composite nanofibers. Put the composite nanofibers into a tubular furnace, and heat it from 25℃ to 300℃ at a heating rate of 5℃ / min under air flow and keep it warm for 2h; then pass argon gas, heat it from 300℃ to 700℃ at a heating rate of 5℃ / min and keep it warm for 1h, finally heat it from 700℃ to 1400℃ at a heating rate of 10℃ / min and keep it warm for 1h, and then cool it to room temperature to obtain SiC nanowhiskers. The scanning electron microscopy of SiC nanowhiskers is as follows Figure 1 As shown, the surface of the SiC whisker is rough, the diameter of the whisker is about 150-300 nm, and the whisker contains a large number of microporous structures. The presence of the microporous structure greatly increases its specific surface area, further improving its compatibility with the matrix resin.
[0045] (4) Preparation of bio-based epoxy resin wear-resistant and anti-corrosion coatings
[0046] Add 0.04g modified SiO2, 0.01g SiC nanowhisker and 40g epoxy resin into 100g distilled water, stir and disperse them evenly with a high-speed disperser at 500rpm, then add 6g fatty amine curing agent, 1g polysiloxane defoaming agent and 2g polyvinyl alcohol leveling agent respectively, adjust the speed from 500rpm to 1000rpm and stir and disperse for 10min to obtain a bio-based epoxy resin wear-resistant and anti-corrosion coating.
[0047] Example 2
[0048] (1) Preparation of epoxy resin
[0049] 12g of cardanol was mixed with 4g of formic acid, stirred at room temperature overnight, and then 30mL of 35% hydrogen peroxide was added to the above solution. After the addition was completed, the reaction was stirred magnetically at 65°C for 1h, and the crude product was extracted with 100mL of ethyl acetate, and the product was neutralized with saturated sodium bicarbonate solution. The organic phase was collected, the product was dried with anhydrous sodium sulfate, and concentrated under reduced pressure to obtain a reddish brown viscous liquid epoxy resin.
[0050] (2) Preparation of modified SiO2
[0051] Add 3g ammonia water, 50g ethanol, 120g deionized water and 0.40g hexadecyltrimethylammonium bromide into a three-necked flask, add 2.0g tetraethyl orthosilicate and 0.7g Γ-glycidyloxypropyltrimethoxysilane under stirring, heat to 55℃, and react with magnetic stirring for 24h. The product is centrifuged, washed and dried to obtain epoxidized SiO2 white powder. Dissolve 0.30g epoxidized SiO2 in 120mL deionized water and disperse ultrasonically to obtain SiO2 dispersion; dissolve 0.60g octadecylamine in 100mL anhydrous ethanol. Add the octadecylamine solution to the SiO2 dispersion, react with magnetic stirring at 25℃ for 24h, wash and dry the product to obtain modified SiO2 white powder.
[0052] (3) Preparation of SiC nanowhiskers
[0053] 1g polyacrylonitrile and 0.2g nano-SiO2 powder were added to 20g N,N-dimethylacetamide solvent, and the solution was stirred magnetically at room temperature to obtain a precursor dispersion. The dispersion was quenched in a -20℃ low-temperature refrigerator for 3h, then extracted in ice water, the solvent was removed, and the mixture was soaked in distilled water for 24h, washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers. The composite nanofibers were placed in a tubular furnace, and heated from 25℃ to 300℃ at a heating rate of 5℃ / min under air flow and kept warm for 2h; then, argon was passed through, and the temperature was increased from 300℃ to 700℃ at a heating rate of 5℃ / min and kept warm for 1h, and finally, the temperature was increased from 700℃ to 1400℃ at a heating rate of 10℃ / min and kept warm for 1h, and then reduced to room temperature to obtain SiC nanowhiskers.
[0054] (4) Preparation of bio-based epoxy resin wear-resistant and anti-corrosion coatings
[0055] Add 0.05g modified SiO2, 0.02g SiC nanowhisker and 50g epoxy resin into 80g distilled water, stir and disperse them evenly with a high-speed disperser at 500rpm, then add 8g fatty amine curing agent, 1.5g polysiloxane defoaming agent and 1g polyvinyl alcohol leveling agent respectively, adjust the speed from 500rpm to 1000rpm and stir and disperse for 10min to obtain a bio-based epoxy resin wear-resistant and anti-corrosion coating.
[0056] Example 3
[0057] (1) Preparation of epoxy resin
[0058] 12g of cardanol was mixed with 4g of formic acid, stirred at room temperature overnight, and then 30mL of 35% hydrogen peroxide was added to the above solution. After the addition was completed, the reaction was stirred magnetically at 65°C for 1h, and the crude product was extracted with 100mL of ethyl acetate, and the product was neutralized with saturated sodium bicarbonate solution. The organic phase was collected, the product was dried with anhydrous sodium sulfate, and concentrated under reduced pressure to obtain a reddish brown viscous liquid epoxy resin.
[0059] (2) Preparation of modified SiO2
[0060] Add 3g ammonia water, 50g ethanol, 120g deionized water and 0.40g hexadecyltrimethylammonium bromide into a three-necked flask, add 2.0g tetraethyl orthosilicate and 0.7g Γ-glycidyloxypropyltrimethoxysilane under stirring, heat to 55℃, and react with magnetic stirring for 24h. The product is centrifuged, washed and dried to obtain epoxidized SiO2 white powder. Dissolve 0.30g epoxidized SiO2 in 120mL deionized water and disperse ultrasonically to obtain SiO2 dispersion; dissolve 0.60g octadecylamine in 100mL anhydrous ethanol. Add the octadecylamine solution to the SiO2 dispersion, react with magnetic stirring at 25℃ for 24h, wash and dry the product to obtain modified SiO2 white powder.
[0061] (3) Preparation of SiC nanowhiskers
[0062] 1g polyacrylonitrile and 0.2g nano-SiO2 powder were added to 20g N,N-dimethylacetamide solvent, and the solution was stirred magnetically at room temperature to obtain a precursor dispersion. The dispersion was quenched in a -20℃ low-temperature refrigerator for 3h, then extracted in ice water, the solvent was removed, and the mixture was soaked in distilled water for 24h, washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers. The composite nanofibers were placed in a tubular furnace, and heated from 25℃ to 300℃ at a heating rate of 5℃ / min under air flow and kept warm for 2h; then, argon was passed through, and the temperature was increased from 300℃ to 700℃ at a heating rate of 5℃ / min and kept warm for 1h, and finally, the temperature was increased from 700℃ to 1400℃ at a heating rate of 10℃ / min and kept warm for 1h, and then reduced to room temperature to obtain SiC nanowhiskers.
[0063] (4) Preparation of bio-based epoxy resin wear-resistant and anti-corrosion coatings
[0064] Add 0.03g modified SiO2, 0.015g SiC nanowhiskers and 45g epoxy resin into 90g distilled water, stir and disperse them evenly with a high-speed disperser at 500rpm, then add 7g fatty amine curing agent, 2g polysiloxane defoaming agent and 1g polyvinyl alcohol leveling agent respectively, adjust the speed from 500rpm to 1000rpm and stir and disperse for 10min to obtain a bio-based epoxy resin wear-resistant and anti-corrosion coating.
[0065] Comparative Example 1
[0066] The only difference between this comparative example and Example 1 is that modified SiO2 and SiC nano whiskers are not added.
[0067] Comparative Example 2
[0068] The only difference between this comparative example and Example 1 is that no SiC nano whiskers are added.
[0069] Comparative Example 3
[0070] The only difference between this comparative example and Example 1 is that no modified SiO2 is added.
[0071] Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 and Table 2:
[0072] Table 1 Components and ratios of Examples 1-3 and Comparative Examples 1-3
[0073]
[0074] Table 2 Coating performance test of Examples 1-3 and Comparative Examples 1-3
[0075] performance Adhesion / Grade hardness Impact resistance (kg·cm) Salt spray resistant Example 1 0 3H 50.2 No corrosion products and rust Example 2 0 3H 49.2 No corrosion products and rust Example 3 0 3H 49.1 No corrosion products and rust Comparative Example 1 1 2H 38.9 Corrosion products and rust Comparative Example 2 0 2H 42.8 No corrosion products and rust Comparative Example 3 1 3H 46.2 Corrosion products and rust
[0076] From the performance test results in Table 2, we can see that:
[0077] (1) In Examples 1-3 of the present invention, the adhesion of the coating is level 0, the hardness is 3H, and the impact strength is 49.1-50.2 kg·cm. The salt spray resistance test shows that after the coating is immersed for 500 hours, the coating does not produce corrosion products and rust, indicating that after adding a small amount of modified SiO2 and SiC nanowhiskers to the coating, the wear resistance and corrosion resistance of the coating are greatly improved.
[0078] (2) Compared with Example 1, in Comparative Example 1, modified SiO2 and calcium carbide nanowhiskers were not added, the adhesion of the coating was level 1, the hardness was 2H, and the impact strength was 38.9. The salt spray resistance test showed that a large amount of corrosion products and rust appeared after the coating was immersed for 500 hours.
[0079] (3) In Comparative Example 2, modified SiO2 is added on the basis of Comparative Example 1. Compared with Comparative Example 1, the adhesion of Comparative Example 2 is improved and the salt spray resistance is also greatly improved. This shows that the addition of modified SiO2 can significantly improve the adhesion and corrosion resistance of the coating.
[0080] (4) In Comparative Example 3, SiC nano whiskers were added on the basis of Comparative Example 1. Compared with Comparative Example 1, the hardness and impact resistance of Comparative Example 3 were greatly improved, indicating that the addition of SiC nano whiskers significantly improved the wear resistance of the coating.
[0081] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A bio-based epoxy resin wear-resistant and anti-corrosion coating composition, characterized in that: It includes the following components by weight:
2. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 1, characterized in that: The preparation method of the epoxy resin is: Mix cardanol and formic acid, stir at room temperature overnight, add hydrogen peroxide, and react to obtain a crude product; The crude product was extracted with ethyl acetate, neutralized with saturated sodium bicarbonate solution, and the organic phase was collected; The organic phase was dried over anhydrous sodium carbonate and concentrated under reduced pressure to obtain an epoxy resin.
3. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 2, characterized in that: The mass concentration of the hydrogen peroxide is 35%; the mass ratio of the cardanol to formic acid is (3-10): (1-3).
4. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 1, characterized in that: The preparation method of the modified SiO2 is: After ammonia water, ethanol, deionized water and hexadecyltrimethylammonium bromide are mixed, tetraethyl orthosilicate and γ-glycidyloxypropyltrimethoxysilane are added, and the mixture is reacted at 50-60°C to obtain epoxidized SiO2; Dispersing the epoxidized SiO2 in deionized water to obtain a SiO2 dispersion; Dissolve octadecylamine in anhydrous ethanol, mix well, and add into the SiO2 dispersion. After reaction, modified SiO2 is obtained.
5. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 4, characterized in that: The mass ratio of the epoxidized SiO2 to octadecylamine is (2-4):(6-10).
6. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 1, characterized in that: The preparation method of the SiC nano whisker is: Adding polyacrylonitrile and nano-SiO2 powder into N,N-dimethylacetamide solvent and dispersing them evenly, a precursor dispersion is obtained; The precursor dispersion is subjected to low temperature quenching, and then transferred into ice water for extraction to remove the N,N-dimethylacetamide solvent, and then washed and dried to obtain polyacrylonitrile / SiO2 composite nanofibers; The polyacrylonitrile / SiO2 composite nanofibers are heated to 250-350°C at a rate of 2-8°C / min in air, kept warm for 2 hours, then transferred to an argon atmosphere, heated to 650-750°C at a rate of 2-8°C / min, kept warm for 1 hour, and finally heated to 1200-1600°C at a rate of 8-12°C / min, kept warm for 1 hour to obtain SiC nanowhiskers.
7. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 6, characterized in that: The mass ratio of polyacrylonitrile to nano-SiO2 powder is (2-5):(1-2); the temperature of low-temperature quenching is -30--10°C, and the quenching time is 3-5h.
8. The bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 1, characterized in that: The curing agent is selected from fatty amine curing agents; the defoaming agent is selected from polysiloxane defoaming agents; and the leveling agent is selected from polyvinyl alcohol leveling agents.
9. A method for preparing the bio-based epoxy resin wear-resistant and anti-corrosion coating composition according to claim 1, characterized in that: The steps include: The modified SiO2, SiC nano whiskers and epoxy resin are added into distilled water, stirred and dispersed evenly at a speed of 500 rpm, and then a curing agent, a defoaming agent and a leveling agent are added and dispersed at a speed of 1000 rpm to obtain the bio-based epoxy resin wear-resistant and anti-corrosion coating.
10. Use of the bio-based epoxy resin wear-resistant and anti-corrosion coating as claimed in claim 1 in a centrifugal wear-resistant slurry pump.
Citation Information
Patent Citations
Preparation method of silicon-series nano-fiber reinforcing agent
CN108221087A
Nano-modified epoxy resin anticorrosive paint and preparation method thereof
CN110669408A
Water-based ceramic anticorrosive coating composition as well as preparation method and application thereof
CN110713777A
Preparation method of hydrophobic composite anti-corrosion coating and application thereof
CN113583543A
Functionalized silicon dioxide toughened epoxy resin coating and preparation method thereof
CN115011215A
Cited By
Bio-based water-based thick epoxy anticorrosive paint and preparation method thereof
CN121718241A
